EFEKTIVITAS PEMBELAJARAN TEMATIK KELAS II DI MADRASAH IBTIDAIYAH SWASTA MA’HAD AL-ZAYTUN, INDRAMAYU SEMESTER GANJIL TAHUN AJARAN 2017/2018 - Kulsum, Syayidah; Rahim, Abdur (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
Thematic learning is one of the models in integrated learning (integrated instruction) which is a learning system that allows students, both individually and in groups, to actively explore and discover scientific concepts and principles in a holistic, meaningful, and authentic way. Integrated learning is oriented towards learning practices that suit the needs and development of students. This approach departs from learning theory which rejects the process of training/memorization (drill) as the basis for the formation of knowledge and the intellectual structure of children. The purpose of this research is to serve as a reference in overcoming the problems faced in the implementation of education so that countermeasures can be sought to be used as material for consideration in making educational development policies. This type of research is field research with a qualitative approach. The research instruments used in this study include observation guidelines, interview guidelines, and documentation. Data analysis techniques are data analysis and interpretation techniques. Miles and Huberman's research analysis model goes through the stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that, (1) thematic learning plans for second grade students at Ma'had AL-Zaytun Indramayu Private Madrasah Ibtidaiyah have fulfilled all the elements needed in thematic learning planning. (2) The implementation of thematic learning for class II students at Ma'had Al-Zaytun Indramayu Private Madrasah Ibtidaiyah has been going well and fulfilling the correct learning stages. (3) Thematic learning for class II students at Ma'had AL-Zaytun Indramayu Private Madrasah Ibtidaiyah has been effective and achieved learning objectives in general.